2018
DOI: 10.1515/humo-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity of female students in secondary schools in the context of physical activity recommendations fulfilment

Abstract: Purpose. Increasing energy intake and decreasing movement performance are among the greatest population issues of mankind. Risk elimination consists in returning to physically active way of life. The aim of the paper was to analyse the physical activity of female in selected secondary schools in the Presov district region, Slovakia, from the point of view of physical activity recommendations fulfilment. Methods. The research group consisted of 353 female students from 14 selected secondary schools in the Preso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Physical activity can be defined as any bodily movement produced by skeletal muscles that results in energy expenditure [1]. A minimum amount of physical activity is necessary for a healthy development of an organism [2]. Also, undertaking regular physical activity plays a considerable role in preventing a variety of diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity can be defined as any bodily movement produced by skeletal muscles that results in energy expenditure [1]. A minimum amount of physical activity is necessary for a healthy development of an organism [2]. Also, undertaking regular physical activity plays a considerable role in preventing a variety of diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Students from all three countries had higher levels of PA than the Polish students examined by Maciaszek et al and in comparison to the students presented in this article. Czech students were recognized as being the most active students from European countries [ 51 , 52 ]. Sedentary behaviors in the presented study expressed as a total sitting component (min per week) were worse than other Polish student populations [ 48 ] and Scandinavian students.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that lifestyle, nutritional behavior and medications can modify lipid status [25]. The studies of Bergier et al and Junger et al have shown that boys are more active than girls, while girls, who in a very small percentage fulfill the physical activity recommendations, have better nutritional behavior [27,28]. Also, an association between the PRDM16 and CtBP2 genotypes and TC was observed only in the population of healthy adolescents, and the long-term health impact of this association is not clear.…”
Section: Discussionmentioning
confidence: 99%